Beneficiile de asistenţă socială gestionate de Ministerul Muncii, Familiei şi Protecţiei Sociale - Stănescu, Simona Maria; Dragotoiu, Adina; Marinoiu, Alina Ioana (Calitatea Vieții, 2012)
The article analyses the social work system from the social benefits’ perspective. The starting question was: how is the trajectory of social assistance’ system in Romania, taking into account the communist legitimacy and the impact of adopting various design options of post-communist social policies? First part of the article is focused on the conceptual framework, with special attention paid on contributive – non-contributive systems, the presentation of main elements of European context, as well as communist and post-communist regulations in the field of social assistance. The second part of the article detailed the evolution of Romanian social benefits assembly, from the institution building and normative views. The analysis of social benefits assembly in Romania emphasized a rather reactive character facing the social problems, than a strategic vision able to anticipate and plan. Implementing such a vision for development of social assistance system in Romania depends on the assessment and monitoring of social benefits, including the impact of providing each of them.